2016 مظاهر تدخل ورقابة رئيس الجمهورية للعمل التشريعي في ظل التعديل الدستوري لسنة - غريسي, جمال; غريسي, العيد (جامعة الوادي University of Eloued, 2019)
إن المركز القانوني لرئيس الجمهورية في الدساتير الجزائرية، يلفت انتباه الباحث، وخاصة في علاقته مع السلطة التشريعية اذا قبلنا بتكريس مبدأ الفصل بين السلطات في التعديل الدستوري لسنة 2016، فقد أقر هذا التعديل لرئيس الجمهورية صلاحيات عديدة تجعله يتدخل ويراقب العمل التشريعي، منها ما يكون داخل قبة البرلمان، أي أثناء مراحل اعداد القوانين، ومنها ما يكون خارج قبة البرلمان، أي في المراحل المنفصلة عن إعداد القانون، وهو ما يجعل الباحث عن تكريس مبدأ الفصل بين السلطات في هذا التعديل، يقر بعدم وجوده، مقارنة بالصلاحيات الممنوحة للسلطة التنفيذية في الرقابة والتدخل في العمل التشريعي، وهي ما زادت من قوة المركز القانوني لرئيس الجمهورية. The legal status of the President of the Republic in Algerian Constitutions draws the attention of the researcher, especially when it comes to his relations with the legislature, if we accept the establishment of the separation of powers principle set by the constitutional amendment of 2016. The new constitutional amendment acknowledged to the President of the Republic many powers that would allow him to monitor and interfere in the legislative process. Some of these powers are to be exercised in the parliament, in the legislation process, and some are be exercised outside the parliament, not during the law preparation process, which forces the researcher pursuing the consecration of the principle of separation of powers by this amendment, to recognize its absence, compared to the powers Granted to the executive authority in the control and intervention in the legislative process, which increases the strength of the President of the Republic's legal status.
Aspects Of Intervention & Control Of Legislative Work By The President Of The Republic Under The Constitution Of 2016 2016
Keywords: مظاهر تدخل رئيس الجمهورية، رقابة البرلمان، العمل التشريعي; Aspects Intervention President of the Republic, control, Parliament, Legislative Process